Pattern and trends of respiratory diseases in an outpatient setting: a five-year review in a tertiary hospital in South-South, Nigeria - Emorinken, Airenakho; Agbadaola, Oluwaseun R.; Akpasubi, Blessyn O.; Ugheoke, Asuwemhe J.; Dic-Ijiewere, Mercy O.; Izirein, Hannah O.; Ibeji, Chidinma U.; Barrah, John C.; Irumudomon, Jessy G. (International Journal of Research in Medical Sciences, 2023)
Background: Limited information exists on the epidemiology of respiratory diseases in South-South Nigeria, especially regarding changing risk factors. This study aimed to assess the frequency and pattern of respiratory diseases in an adult outpatient clinic in a teaching hospital in South-South Nigeria. Methods: Medical records of newly referred patients with respiratory diseases who received care at the chest clinic of Irrua Specialist Teaching Hospital from January 2018 to December 2022 were retrospectively reviewed. Results: The study included 655 patients (mean age: 54.7±18.7 years). The majority of cases occurred in the 41-60 age group, and 55.4% were female. Non-communicable respiratory diseases accounted for 60.9% of cases, while communicable respiratory diseases accounted for 39.1%. The most common respiratory diseases observed were bronchial asthma (22.6%), tuberculosis (21.1%), chronic obstructive pulmonary disease (19.2%), pneumonia (11.1%), interstitial lung diseases (6.7%), and lung cancer (4.1%). Less common respiratory diseases included pulmonary aspergilloma (1.5%), pleural-related diseases (0.8%), hypersensitivity pneumonitis (0.8%), and obstructive sleep apnoea syndrome (0.6%). The study's annual trend showed a gradual increase in the number of respiratory cases, reaching a low point in 2020. Significant differences were found in the age and gender distribution of the top six respiratory diseases (p <0.001). Conclusions: This study provides valuable insights into the demographic and disease patterns of respiratory diseases in an outpatient setting, informing targeted prevention and treatment measures for these conditions.